A framework for integrating sustainable production practices along the product life cycle - Mohamed A.E. Omer; Ahmed Mohamed Mahmoud Ibrahim; Ammar H. Elsheikh; Hussien Hegab (Environmental and Sustainability Indicators)
In response to urgent global challenges posed by climate change and environmental degradation, integrating sustainable production practices into the entire product life cycle (PLC) has become essential. This paper proposes a comprehensive framework addressing the gap between sustainability models and product life cycle assessment (PLCA), emphasizing the need for a holistic approach encompassing economic, social, and environmental dimensions. The framework outlines optimal sustainable practices from material extraction to end-of-life disposal. It emphasizes reduced ecological footprints, resource conservation, pollution mitigation, and enhanced sustainability. Furthermore, it underscores the role of governmental and non-governmental organizations (GOs and NGOs) in promoting this integrated approach. This research further explores key questions about integrating sustainable practices, implementation challenges, and economic feasibility, aiming to guide businesses toward holistic approaches that balance economic growth, environmental stewardship, and social equity across the entire PLC.